Impact of Cognitive Impairment and Impostor Syndrome on Mental Health Issues among Hemiplegic Stroke Survivors - Sadaf, Ambreen; Iqbal, Muhammad Nasar; Javed, Fatima; Rose , Sybil (Journal of Postgraduate Medical Institute, 2024)
Objective: To determine the impact of cognitive impairment and impostor syndrome on mental health issues among hemiplegic stroke survivors. Methods: A Correlational research design along with a purposive sampling technique was employed on 100 participants to find out the relationship. Data collection was done through the questionnaires i.e., Cognitive Assessment Scale, Clance IP, and DASS-21. Results: Results indicated that 53% of participants were males and 47% were females. 67% of participants were suffering from left hemiplegic while 33% with right hemiplegic. Pearson product-moment correlation analysis revealed that cognitive impairment was significantly positively correlated with impostor syndrome (.42***) and mental health issues (.44***) among hemiplegic stroke survivors. Results also revealed that cognitive impairment and impostor syndrome are both positive predictors of mental health issues (.44***, .54***) among hemiplegic stroke survivors. Independent sample t-test analysis results showed that female survivors had more mental health issues compared to the male participants. Conclusion: This study concluded that cognitive impairment and impostor syndrome have a large effect on mental health issues, i.e., depression, anxiety, and stress. In order to give complete care to hemiplegic stroke survivors, healthcare practitioners, and support networks must fully comprehend these relationships. Mental health problems can be lessened by addressing cognitive deficits and impostor syndrome, offering psychological support, and encouraging self-esteem and resilience.